Vendor Involvement and Concurrent Engineering: Methods in Reducing Development Time For New Model in Automotive Industry - Nik Mohamed, Nik Mohd. Zuki; Sastra, Hasan Yudie; Salit, Mohd. Sapuan; Ismail, Napsiah; Raj Arora, Prithivi; Abdul Hamid, Abu Bakar (Universiti Teknologi Malaysia, 2005)
A study of method improvement to reduce development time for new model in automotive industry is presented in this paper. The approach taken is by studying the existing practice in car development. It was found that in the current practice of car development, project planning and master schedule were not officially endorsed by all related departmental heads, which resulted in too ambitious and unrealistic schedules. Other problem includes lack of comprehensive market research to gauge the car implementation timing, styling and manufacturing trend in the process of project planning. It was also found that benchmarking exercise was carried out on already released product and for future product. The study suggested various ways for method improvement such as through effective benchmarking process, audit of vendor capability, excellent computer facility, official endorsement of project planning and master schedule by related departmental heads and comprehensive market research.